Management of Transplant Renal Artery Stenosis - Rajan, Dheeraj K. (Thieme Medical Publishers, 2004)
Transplant renal artery stenosis is the most frequent vascular complication of transplantation. Early detection and correction reduce patients' morbidity and allograft dysfunction. Although noninvasive imaging can detect an underlying stenosis, angiography with subsequent angioplasty or stenting, or both, provides definitive diagnosis and treatment. With the introduction of alternative contrast agents and newer catheter and stent technology, these procedures can be performed safely with little risk of contrast-induced nephropathy or allograft loss.